Violence against women: Can "jealousy" mitigate the significance of violence? - COSTA, Maria de Nazaré Pereira da (Universidade Federal do Pará, 2017)
Beliefs about love and jealousy can be variables that influence violence against women. The aim of our reproduction of a United States study was to compare our data with those of the original study regarding the acceptance of violence related to jealousy. A total of 264 college students participated in the study. They heard and assessed two audio recordings ("jealousy" and "no jealousy"), but half heard situations in which the husband beat his wife and half situations in which the husband does not beat his wife. After each audio recording, participants answered six questions, among them: "how much the husband loves his wife" and "how long would the relationship last". It was observed that, aggression, in the case of "no jealousy", showed to have a negative meaning both in the United States study and in the present study, which was not observed in the case of "jealousy". It may be concluded that violence against women is a cultural practice in Brazil and that social rules regarding male honor, female submission and jealousy exert influence on this practice.